Multiple rapid swallows and rapid drink challenge in patients with esophagogastric junction outflow obstruction on high‐resolution manometry. Issue 3 (11th October 2020) - Krause, Amanda J.; Su, Hui; Triggs, Joseph R.; Beveridge, Claire; Baumann, Alexandra J.; Donnan, Erica; Pandolfino, John E.; Carlson, Dustin A.
Abstract: Background: Esophagogastric junction outflow obstruction (EGJOO) as defined by Chicago Classification of esophageal motility disorders (CCv3.0) encompasses a broad range of diagnoses, thus posing clinical challenges. Our aims were to evaluate multiple rapid swallow (MRS) and rapid drink challenge (RDC) during high‐resolution manometry (HRM) to aid identifying clinically relevant EGJOO. Methods: Patients with a HRM diagnosis of EGJOO based on CCv3.0 that also completed MRS and RDC during HRM and barium esophagram were retrospectively identified. Radiographic EGJOO (RAD‐EGJOO) was defined by either liquid barium retention or delayed passage of a barium tablet on barium esophagram. Thirty healthy asymptomatic controls that completed HRM were also included. MRS involved drinking 2 mL for 5 successive swallows. RDC involved rapid drinking of 200 mL liquid. Integrated relaxation pressure (IRP) and presence of panesophageal pressurization (PEP) during MRS and RDC were assessed. Key Results: One hundred one patients, mean (SD) age 56 (16) years, were included; 32% had RAD‐EGJOO, 68% did not. RAD‐EGJOO patients more frequently had elevated (>12 mmHg) upright IRP (100%), MRS‐IRP (56%), RDC‐IRP (53%), and PEP during RDC (66%) than both controls [17%; 0%; 7%; 3%] and patients without RAD‐EGJOO [83%; 35%; 39%; 41%] Having IRP >12 mmHg during both MRS and RDC was twice as likely to be associated with RAD‐EGJOO (19%) than those without RAD‐EGJOO (9%) among patients with upright IRP >12 mmHg. Conclusions and Inferences: Adjunctive HRM maneuvers MRS and RDC appear to help identify clinically significant EGJOO. While future outcome studies are needed, comprehensive multimodal evaluation helps clarify relevance of EGJOO on HRM. Abstract : High‐resolution manometry (HRM) maneuvers, multiple rapid swallows and rapid drink challenge, helped identify patients with retention on barium esophagram among patients classified as esophagogastric junction outflow obstruction (EGJOO) on HRM; thus these test maneuvers may be helpful in differentiating clinically relevant EGJOO from misleading pressure artifact.